The Way Forward: The Power of Diversity - Muto, Ako (Human Security Norms in East Asia, 2018)
This chapter wraps up the discussion of all chapters by incorporating perspectives of JICA practitioners. We can advance the human security practice in the three dimensions: national, regional, and global. In the national dimension, capacity development and empowerment will play a key role. In the regional dimension, the diversity of “ASEAN Plus Three” can be the source of dynamic community formation in East Asia. In the global dimension, human security can effectively supplement the Sustainable Development Goals (SDGs) by means of its emphasis on risks and vulnerability. Finally, the entanglement of human security and responsibility to protest (R2P) is discussed. Making much of national ownership and dignity, human security is expected to reinforce its influence in East Asia and worldwide.